Forage legumes in crop-livestock systems of sub-Saharan Africa - Saka, A.R.; Haque, I.; Lupwayi, N.Z.; El-Wakeel, A. (International Livestock Centre for Africa, 1994)
This document starts by describing the five main agroecological zones of sub-Saharan Africa, viz, arid, semi-arid, subhumid, humid, and highland, and summarising population and agricultural production. Then it goes to the main topics that includes inter cropping systems; criteria for evaluating the productivity and efficiency of inter cropping systems; some agronomic factors influencing the productivity and efficiency of inter cropping systems; resource use and competition among system components; the role of nitrogen in inter cropping systems; and improving feed quality through forage legumes-cereal inter cropping in crop-livestock systems.